Pharmacokinetic interaction between tadalafil and bosentan in healthy male subjects - Wrishko, Rebecca E; Dingemanse, Jasper; Yu, Albert; Darstein, Christelle; Phillips, Diane L; Mitchell, Malcolm I (Journal of clinical pharmacology, 2008)
Tadalafil, an oral phosphodiesterase 5 (PDE5) inhibitor, is being investigated as a treatment for pulmonary arterial hypertension. Bosentan is an oral endothelin receptor antagonist widely used in the treatment of pulmonary arterial hypertension. Tadalafil is mainly metabolized by cytochrome P450 (CYP) 3A4, and as bosentan induces CYP2C9 and CYP3A4, a pharmacokinetic interaction is possible between these agents. This open-label, randomized study investigated whether any pharmacokinetic interaction exists between tadalafil and bosentan. Healthy adult men (n = 15; 19-52 years of age) received 10 consecutive days of tadalafil 40 mg once daily, bosentan 125 mg twice daily, and a combination of both in a 3-period, crossover design. Following 10 days of multiple-dose coadministration of bosentan and tadalafil, compared with tadalafil alone, tadalafil geometric mean ratios (90% confidence interval [CI]) for AUCtau and Cmax were 0.59 (0.55, 0.62) and 0.73 (0.68, 0.79), respectively, with no observed change in tmax. Following coadministration of bosentan with tadalafil, bosentan ratios (90% CI) for AUCtau and Cmax were 1.13 (1.02, 1.24) and 1.20 (1.05, 1.36), respectively. Tadalafil alone and combined with bosentan was generally well tolerated. In conclusion, after 10 days of coadministration, bosentan decreased tadalafil exposure by 41.5% with minimal and clinically irrelevant differences (<20%) in bosentan exposure.